Vida, paixão e obra: sentidos em Paulo Leminski - Passos, Lucas dos (2016)
The analysis of Paulo Leminski herein proposed – dedicated to peer, in the materiality of the poet’s texts, the paths between life, oeuvre and history – demands some methodological steps. In the first part of this thesis, the constitution of the character-writer Paulo Leminski is put under perspective – in life and in death –, with the aid of the author’s own words, of texts from print media (specifically features and articles from Veja and Folha de São Paulo, in the 1980s) and of more or less specialized criticism; in the second, the focus falls into the inquietudes of aesthetic and political order that the poet concentrated in the novella “Minha classe gosta / Logo, é uma bosta” and, furthermore, into the autobiographical essays (specially the text about Trótski), that widen the historical and literary concerns of the leminskian opus; finally, in the third part, the poetic machinery of Leminski (in its rhythmic intricacies and ponderations regarding the existing fold between life and poem) is observed, as well as the movements betwixt the personal history and the collective history accomplished in the formal composition of “Verdura”, a fundamental stone in the approach of the poet to popular song. This path, in addition to the leminskian critical fortune, will count upon the support of [a] the works of Paula Sibilia (O show do eu: a intimidade como espetáculo) and A. Alvarez (A voz do escritor) about the cult of artistic personality; [b] writings by Walter Benjamin (specially “As afinidades eletivas de Goethe” and “Sobre dois poemas de Friedrich Hölderlin”) about the relations between literature and life; [c] studies of Theodore Adorno (mainly in Teoria estética and Notas de literatura) on the relations between literary form and historic matter; [d] essays by Giorgio Agamben (“O fim do poema” and Ideia da prosa) and from Alfredo Bosi (in O ser e o tempo da poesia) about the relations between poetry, enjambment and silence, as well as Introdução ao Zen-budismo, by Daisetz Suzuki, which also illuminates the question of silence, in the way captured by Leminski; and [e] texts from Luiz Tatit (“Elementos para a análise da canção”) and Cláudia Neiva de Mattos (“Poesia e Música: laços de parentesco e parceria”) about the analysis of the song genre.